Heat transfer analysis of the forced air quenching with non-isothermal and non-uniform oxidation. - Yue Zhang (Public Library of Science (PLoS), 2021)
In this paper, the heat transfer characteristics of the forced air quenching with non-isothermal and non-uniform oxidation are investigated. By introducing the variations of interfacial temperature and oxygen partial pressure, a three-layered non-isothermal high-temperature oxidation kinetic model is developed, in which a discrete-time modeling method is employed to solve the problem of integration of the transient terms, and a special interfacial grid treatment is used for considering the growth of each oxide layer and updating of the thermal properties. Moreover, a parameter identification method using the multi-objective genetic algorithm is proposed for the inverse solution of the oxidation parabolic parameters based on the measured scale thicknesses in oxidation experiment. A case study of the forced air quenching of a Q235 disk is presented to validate the availability of the developed formulas. Then the interfacial heat transfer characteristics are analyzed, while the numerical solutions with and without oxidation are both performed for in-depth comparison. Results indicate that the active quenching region is mainly centralized in the vicinity of stagnation region. The radial variation regularity of the temperature difference across the total oxide layer is mainly determined by the thermal conductivity and the scale thickness. The existence of the oxide scale actually produces a certain thermal resistance during the quenching process and the effects of the oxide scale increases with the radial coordinate due to the interfacial temperature distribution. The results obtained can provide theoretical derivation for precise control of the internal phase transformation during the forced air quenching process.